Novice teachers’ knowledge of effective study strategies - Surma, Tim; Camp, Gino; de Groot, Renate; Kirschner, Paul A. (Frontiers in Education, 2022)
This survey research, assessed whether novice secondary school teachers knew and understood the effectiveness of empirically-supported learning strategies, namely spaced practice, retrieval practice, interleaved practice, using multimodal representations, elaborative interrogation and worked-out examples. These ‘proven’ strategies can be contrasted with frequently used learning strategies that have been found to be less effective, such as re-reading, taking verbatim notes, highlighting/underlining, summarizing, and cramming. This study broadens previous research on teachers’ knowledge of learning strategies by both refining and extending the methodology used in the scenario studies, and by administering it to a different, previously unexplored population. Novice teachers enrolled in a teacher training program (N=180) in Flanders, Belgium were presented with a three part survey, consisting of open-ended questions, learning scenarios and a list of study strategies. The results show that misconceptions about effective study strategies are widespread by novice teachers and suggests that they are unaware of several specific strategies that could benefit student learning and retention. While popular but less effective strategies such as highlighting and summarising were commonly named by them in open-ended questions, this was not the case for proven effective strategies (e.g., studying worked-out examples, interleaving, and using multi-modal representations) which were not or hardly mentioned. We conclude that this study adds to the growing literature that it is not only students, but also novice teachers who make suboptimal metacognitive judgments when it comes to study and learning. Explicit instruction in evidence-informed learning strategies should be stressed and included in both teacher professional development programs and initial teacher training.